A Mechanized Harvesting and Automated Grading Technology for Oil Palm Fruit - Saraf, Akshay; Kenkre, Rajdutt; Pinto, Nigel; Fernandes, Blossom (International Journal of Computer Sciences and Engineering, 2025)
The purpose of this research is to design and fabricate an automated grading cum harvesting device for Oil Palm Fruits. The presence of the VIRESCENS or NIGRESCENS gene in oil palm fruits renders it possible to determine the ripeness of the fruit by mere inspection. However, this method of inspection by workers is time-consuming and error-prone. Harvesting of oil palm fruits has been aided by numerous technologies such as the pole and knife method, aluminium pole and knife (APK) method and the like. These manual methods, besides consuming the time and energy of the harvester, pose a serious threat to the safety of the harvester, as he/she runs the risk of being hit by a falling oil palm branch